Research on the path of integrating confucian ethical thoughts into college students’ moral education - Du Xingdong; Huat, Khor Teik (Journal of Islamic, Social, Economics and Development, 2024)
As an important part of Chinese excellent traditional culture, Confucian ethical thoughts can promote the development of traditional culture and modern education by integrating it into moral education. Confucian ethical thoughts can help to excavate the humanistic spirits and values in traditional culture, and at the same time, they are combined with the goals and needs of modern education to provide enlightenment for contemporary education. In view of this, this paper expounds the main contents of Confucian ethical thoughts, analyzes the problems existing in the integration of Confucian ethical thoughts into college students' moral education, and puts forward that it is of great importance to play the role of curriculum education, cultural education, practical education and network education, and promote Confucian ethical thoughts into the classroom, practice platform and cyberspace to promote the overall and effective improvement of college students' moral education.